Enhanced photoluminescence property of sulfate ions modified YAG:Ce3+ phosphor by co-precipitation method - Que, Meidan (2017)
The sulfate ions modified YAG:Ce3+ phosphors were prepared by co-precipitation method and characterized by X-ray diffraction, transmission electron microscopy, and photoluminescence. Effects of sulfate ions on the photoluminescence (PL) property of the as-prepared YAG:Ce3+ phosphors were studied, with sodium dodecyl sulfate (SDS) being added to R3+ (Ce3+, Y3+, Al3+) ions. Results indicated that pure YAG:Ce3+ phosphors with different ratios of sulfate ions could be easily obtained by calcining the as-synthesized precursor at 950 °C for 2 h, the YAG:Ce3+ phosphors with an optimal mass ratio of 3.5 wt.% SDS had the highest emission intensity and the best dispersion behavior, and the fluorescence decay of the as-obtained YAG:Ce3+ phosphors was related to the lattice defect, reabsorption and cross correlation. Furthermore, thermal quenching properties of the YAG:Ce3+ phosphors and the YAG:Ce3+ phosphors with 3.5 wt.%SDS were also discussed, indicating that the YAG:Ce3+ with SDS phosphors could have potential applications in the daylight LEDs or warm white LEDs.